Detection of the breakpoint cluster region-ABL fusion in chronic myeloid leukemia with variant Philadelphia chromosome translocations by in situ hybridization - Tosi Cambini, Sabrina; Cabot, Georges-Philippe; Giudici, Giovanni; Attuati, Viviana; Morandi, Paolo; Rambaldi, Alessandro; Döhner, Hartmut; Biondi, Andrea (Cancer genetics and cytogenetics, 1996)
Fluorescence in situ hybridization (FISH) technique has been successfully used to detect the BCR-ABL gene fusion in chronic myeloid leukemia (CML) with the classic form of the Philadelphia chromosome (Ph). We applied FISH to study three CML patients showing variant Ph chromosome (either complex or simple type). The results demonstrate that the use of a yeast artificial chromosome (YAC)-derived probe (D107F9) and a cosmid probe (cos-abl 8), specific for BCR and ABL genes respectively, allows also the detection of the BCR-ABL fusion in CML patients with variant Ph.
Elektronische Reproduktion der Druck-Ausgabe 19. März 1999
Gesehen am 31.10.2024